2013
DOI: 10.5539/jas.v5n8p142
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Black Bengal Buck Based on Some Reproductive Performance of Their Progeny at Semi-Intensive Rearing System

Abstract: The objective of this study was to select Black Bengal Buck Based on some reproductive performance of their progeny. The least-squares means for overall reproductive performances of age of first kidding (AFK), weight at first kidding (WFK), gestation length (GL), kidding interval (KI), post-partum heat (PPT), litter size at birth (LS) and litter weight at birth were 465.6 days, 13.22 kg, 145.34 days, 302.5 days, 123.84 days, 1.61 and 1.66 kg, respectively. The effect of flock and generation were significant (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
(29 reference statements)
3
10
3
Order By: Relevance
“…The finding of the present study also corroborates with earlier reports of 181.23±4.55 and 190.2±0.20 days, respectively as obtained by Faruque et al, (2010) and Hasan et al, (2014) for the same breed. On the other hand, Haque et al, (2013) reported 302.5±4.55 days KI for the same genotype, which looks much higher than our study. The variations of KI with wider ranges among investigators within same genotype could be due to difference of management practices, feeding, reproductive care, seasonality or insufficient breeding bucks.…”
Section: Kidding Interval (Ki)contrasting
confidence: 85%
See 2 more Smart Citations
“…The finding of the present study also corroborates with earlier reports of 181.23±4.55 and 190.2±0.20 days, respectively as obtained by Faruque et al, (2010) and Hasan et al, (2014) for the same breed. On the other hand, Haque et al, (2013) reported 302.5±4.55 days KI for the same genotype, which looks much higher than our study. The variations of KI with wider ranges among investigators within same genotype could be due to difference of management practices, feeding, reproductive care, seasonality or insufficient breeding bucks.…”
Section: Kidding Interval (Ki)contrasting
confidence: 85%
“…Earlier, lower AFK of 283.83±31.16 and 360.5days, respectively were reported by Faruque et al, (2010) in an intensive system and Hassan et al, (2007) for the same breed. However, very higher estimates of AFK were reported by Hassan et al, (2010) (448-450 days) and Haque et al, (2013) (465.6±12.45 days) for the same genotype. Variations within same genotype could be due to variable environment, management and feeding provided by the farmers.…”
Section: Age At First Kidding (Afk)mentioning
confidence: 58%
See 1 more Smart Citation
“…The Black Bengal goat is a breed of goat found throughout Bangladesh and other places of India such as West Bengal, Bihar, and Odisha. One of the most favorable attributes of the Black Bengal goat as a meat-producing animal is its high rate of reproduction and the fact that it has an extended breeding, especially as reproduction is a major contributing factor to the efficiency of meat production [ 5 ]. This breed can adapt to any environment easily and its immunity is very high.…”
Section: Introductionmentioning
confidence: 99%
“…The present finding corroborates with the earlier report of Das et al [15] in Bengal goats of West Bengal. But, higher estimates were reported by Haque et al [16] and Singh et al [17].…”
Section: Resultsmentioning
confidence: 69%